EVALUASI KAPASITAS PENGOLAHAN AIR LIMBAH RUMAH SAKIT (STUDI PADA RUMAH SAKIT X KOTA SURABAYA) - Riris Utami Wulandari; Raden Kokoh Haryo Putro; SeptinAulidia (Yayasan Nusantara Hasana Berdikari, 2023)
The hospital is a health service facility which is one of the many business activities that contribute waste to in an area. Evaluation of Wastewater Treatment Capacity is carried out by analyzing each treatment unit based on the theory in the literature using secondary data obtained from field studies at X Surabaya Hospital. The analysis includes calculating the discharge of liquid wastewater based on the average use of clean water by patients/beds, the average outpatients, and the number of employees. The amount of clean water used in X Hospital based on the number of employees, inpatients, and average outpatient is 561 m 3 /day. The total use of clean water based on the existing condition of the PDAM is 364,760 m3 /day. When compared with the amount of clean water used according to the literature, the results are far inverse. The IPAL of X Surabaya Hospital is able to accommodate the volume of wastewater based on the wastewater discharge using a literature detention time calculation of 253.49m3 with a WWTP capacity of 282 m3 so that the amount of waste produced is in accordance with the existing conditions of the WWTP.